Organic micromolecule photo-thermal material, evaporator system containing photo-thermal material, preparation method and application of organic micromolecule photo-thermal material
By developing new organic small molecule photothermal materials with small energy gap and wide spectrum absorption, the problems of limited spectral absorption range and low photothermal conversion efficiency of existing materials are solved, and high-efficiency photothermal conversion and water-electricity cogeneration are achieved , supports solar-powered thermoelectric production and evaporation water production.
Patent Information
- Application Number
- CN202411424564.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The existing organic small molecule photothermal materials have limited their application in solar energy utilization and water resource regeneration technologies.
A new organic small molecule photothermal material was developed. By adjusting the molecular stacking mode and building D-A structure, the intramolecular charge transfer effect is used to broaden the spectral response range, and free radicals are introduced through chemical modification to optimize the LUMO and HOMO energy levels, and the energy levels of LUMO and HOMO were prepared. Compounds with small energy gaps and wide spectrum absorption are loaded on hydrophilic fabrics to construct flexible evaporators to achieve efficient photothermal conversion and water-to-electricity cogeneration.
It realizes efficient photothermal conversion performance, with a photothermal conversion efficiency of 26.75%. It can quickly heat up to 68℃ under simulated sunlight, and the temperature can reach 140℃ under 4kW m-2 light, and has good light stability. and anti-bleaching properties, supporting solar-powered thermoelectric conversion and water-power cogeneration systems.
Smart Images

Figure CN119306675A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal materials, and in particular relates to an organic small molecule photothermal material and an evaporator system containing the photothermal material, a preparation method and applications thereof. Background Art
[0002] Under the dual challenges of global fossil energy depletion and water shortage, it is particularly important to explore sustainable and clean energy solutions and water resource regeneration technologies. As one of the most abundant and renewable clean energy sources on earth, solar energy, its efficient utilization and conversion technology is becoming a hot topic in scientific research and industry. Among them, solar-driven photothermal-electric conversion technology and interfacial evaporation technology, especially the water-electricity cogeneration system induced by photothermal interfacial evaporation, provide an innovative way to solve the problems of freshwater resource acquisition and clean electricity production at the same time.
[0003] Traditionally, photothermal materials such as precious metals, metal oxides, carbon materials such as graphene, and polymers have shown good application potential in the field of photothermal conversion. However, these materials have varying degrees of limitations in terms of cost, processability, and environmental friendliness. In contrast, organic small molecule photothermal materials have opened up new directions for the research of photothermal conversion materials with their flexibility in structural design, wide tunability of properties, and rich functionalization potential. However, despite their many advantages, organic small molecule photothermal materials still face key challenges in practical applications, such as limited spectral absorption range, low photothermal conversion efficiency, and poor photostability (such as photobleaching).
[0004] In order to overcome these obstacles, researchers are committed to optimizing the performance of organic small molecule photothermal materials through innovative strategies, including: adjusting the molecular stacking mode to enhance light absorption; constructing a DA (donor-acceptor) structure to broaden the spectral response range by using the intramolecular charge transfer effect; introducing intramolecular motion mechanisms to promote energy dissipation and heat release; and introducing free radicals through chemical modification to precisely control the LUMO (lowest unoccupied orbital energy level) and HOMO (highest occupied orbital energy level) of the material, thereby effectively narrowing the band gap and achieving efficient capture of sunlight and photothermal conversion.
[0005] Although preliminary research results have demonstrated the potential of organic small molecule photothermal materials in the field of photothermal-electrical conversion and photothermal interfacial evaporation, the currently reported systems are still relatively limited, the synthesis and preparation are relatively complex, and most systems have not yet reached the standard for practical application in terms of comprehensive performance. Therefore, the development of new organic small molecule photothermal materials with wide spectrum absorption, high photothermal conversion efficiency, and high stability, and the construction of efficient and stable solar-driven water-electricity cogeneration systems based on them have become key scientific issues and technical challenges that need to be urgently addressed. This is not only of great significance for promoting the innovation of solar energy utilization technology, but also provides new ideas and new ways to solve the global water shortage and energy crisis. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide an organic small molecule photothermal material and an evaporator system containing the photothermal material, a preparation method and its application. The photothermal material has excellent photothermal conversion performance. Based on its excellent photothermal conversion performance, it couples temperature difference to produce electricity, and realizes efficient conversion of light, heat and electricity. The photothermal material is loaded on a hydrophilic fabric to construct a flexible evaporator, which can realize efficient interfacial photothermal evaporation and achieve an ideal evaporation rate. It is further used to construct a water-electricity cogeneration system to achieve the synchronous generation of steam and electricity.
[0007] Specifically, the present invention provides an organic small molecule photothermal material, wherein the organic small molecule photothermal material is a compound represented by formula (I):
[0008]
[0009] The invention provides a preparation method of a compound shown in formula (I). The method comprises placing a mixture of tetraamino-p-benzoquinone, tetrabutylammonium bromide and N,N-dimethylformamide in a pressure tube and subjecting it to ultrasonic treatment. The pressure tube is then placed in an oven and heated at 120°C until the reaction is completed. After the reactants are cooled to room temperature, they are filtered or centrifuged to obtain a filter residue. The filter residue is washed with N,N-dimethylformamide and ethanol for multiple times and then dried to obtain a black solid, namely the compound shown in formula (I).
[0010] The present invention also provides an organic small molecule evaporator system, comprising a compound represented by formula (I) and a support material, wherein the compound represented by formula (I) has the following structural formula:
[0011]
[0012] The load material is one of a membrane material, a foam material or a hydrogel material.
[0013] In some specific embodiments of the present invention, the membrane material is at least one of dust-free cloth, non-woven fabric, electrospun nanomembrane and cellulose paper.
[0014] The present invention also provides a method for preparing an evaporator system of an organic small molecule, comprising the following preparation steps: washing the membrane material with ethanol and drying it; dispersing the powder of the compound represented by formula (I) in ethanol, ultrasonicating for 10-30 minutes, and then evenly dripping or brushing the suspension on the dried membrane material, and finally drying it, thereby preparing an evaporator system containing the photothermal material represented by formula (I).
[0015] The present invention also provides a water-electricity cogeneration device, wherein the compound as shown in formula (I) is covered in the middle of a carrier, the middle part of the carrier is fixed to the upper surface (i.e., the hot end) of a thermoelectric device, and the carrier parts without the compound as shown in formula (I) at both ends are in contact with the water body, and polystyrene foam is used as a supporting part to fix the thermoelectric device, so that the lower part (i.e., the cold end) of the thermoelectric device contacts the water surface;
[0016] The structural formula of the compound shown in formula (I) is as follows:
[0017]
[0018] In some specific embodiments of the present invention, the carrier is one of dust-free cloth, non-woven fabric, electrospun nanofilm and cellulose paper.
[0019] The present invention also provides the use of the organic small molecule photothermal material in preparing a photothermal conversion layer or a photothermal functional molecular material.
[0020] The present invention also provides the application of the small molecule photothermal material as claimed in claim 1 in solar-driven thermoelectric conversion, photothermal interface evaporation, water-power cogeneration, sewage treatment and seawater desalination.
[0021] The present invention also provides applications of the organic small molecule evaporator system in solar-driven photothermal interface evaporation, thermoelectric conversion, water-power cogeneration, sewage treatment and seawater desalination.
[0022] The present invention also provides application of the water-power cogeneration device in water-power cogeneration.
[0023] Compared with the prior art, the present invention has the following significant advantages and effects:
[0024] 1. Excellent photothermal conversion performance: The organic small molecule photothermal material provided by the present invention has excellent photothermal performance, a small energy gap (0.77eV), a wide absorption spectrum (250-1840nm), and a photothermal conversion efficiency of up to 26.75% under simulated sunlight. -2 The temperature rapidly rises to 68℃ under simulated sunlight. -2The temperature can reach 140°C under illumination, which is better than most organic small molecule photothermal materials. This efficient photothermal conversion capability provides new possibilities for the thermal utilization of solar energy.
[0025] 2. Strong photostability: The organic small molecule photothermal material provided by the present invention can still maintain consistent temperature changes after multiple heating / cooling cycles; and, after long-term illumination, the temperature can remain stable, showing good photostability and photobleaching resistance, which is crucial for long-term solar energy utilization.
[0026] 3. Wide application fields: Based on the excellent photothermal conversion performance of the organic small molecule photothermal material provided by the present invention, the present invention realizes solar-driven photothermal-electric conversion and photothermal-steam conversion. By using the organic small molecule photothermal material provided by the present invention as a light absorber in combination with a thermoelectric device, it can be used for thermoelectric production; when loaded on a hydrophilic dust-free cloth, a flexible evaporator can be constructed to achieve efficient interfacial photothermal water evaporation. Furthermore, the organic small molecule photothermal material provided by the present invention can also be used to construct a solar-driven water-electricity cogeneration system to achieve the simultaneous generation of steam and electricity, and provide energy and fresh water supply for remote areas.
[0027] In summary, the organic small molecule photothermal material provided by the present invention, as a new type of photothermal material, has shown significant technical advantages in improving solar energy conversion efficiency, stability and broadening the scope of application. These characteristics make it have important application prospects in the field of solar energy utilization, especially in solar-driven thermoelectric production and evaporation water production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 Formula (I) TDT 13 C-NMR spectrum;
[0030] Figure 2 is the FT-IR spectrum of formula (I) TDT;
[0031] Figure 3 is the SEM image of TDT of formula (I);
[0032] Figure 4 is the EDS-mapping diagram of TDT of formula (I);
[0033] Figure 5is the XPS spectrum of formula (I) TDT;
[0034] Figure 6 is the UV-VIS-NIR absorption spectra of the raw material TABQ and TDT of formula (I);
[0035] Figure 7 is the optical band gap diagram of raw material TABQ and TDT of formula (I);
[0036] Figure 8 is the solid state fluorescence emission spectrum and quantum yield of TDT of formula (I);
[0037] Fig. 9 is a thermal infrared imaging diagram of the temperature change of TDT of formula (I) under simulated light;
[0038] Fig.10 is the temperature change curve of TDT of formula (I) under no light intensity;
[0039] Fig.11 is the temperature variation curve of the TDT of formula (I) under intermittent switching lamp (heating / cooling) over time;
[0040] Fig.12 is the temperature change curve of TDT of formula (I) under continuous 2 hours of light;
[0041] Fig.13 The temperature variation curves of the TDT aqueous suspension of formula (I), the raw material TABQ aqueous suspension and pure water under light;
[0042] Fig.14 Schematic diagram of a solar-driven thermoelectric conversion device combining photothermal materials with thermoelectric devices;
[0043] Fig.15 The open circuit voltage and short circuit current generated by solar-driven thermoelectric conversion systems with different configurations under different light intensities;
[0044] Fig.16 The open circuit voltage and short circuit current of the solar-driven thermoelectric conversion system of the load-type (I) TDT under long-term illumination;
[0045] Fig.17 It is a SEM image of a dust-free cloth DF and an evaporator DF / TDT containing TDT of formula (I);
[0046] Fig.18 The SEM image of the evaporator DF / TDT containing TDT of formula (I) and the EDS-mapping image of its element distribution;
[0047] Fig.19is the absorbance of the dust-free cloth DF and the evaporator DF / TDT containing TDT of formula (I) in the wavelength range of 250-2500 nm;
[0048] Fig. 20 The thermal infrared imaging and temperature change curve of the temperature change of the dust-free cloth DF and DF / TDT with different loads of TDT under simulated light;
[0049] Fig.21 Schematic diagram of a solar-powered photothermal water evaporation device;
[0050] Fig. 22 Water evaporation mass loss curve per unit time for different evaporators;
[0051] Fig.23 This is a comparison chart of the evaporation rate of TDT and other organic small molecule-based two-dimensional and three-dimensional evaporators;
[0052] Fig.24 To simulate the comparison of heavy metal ion concentrations in water samples before and after sewage treatment;
[0053] Fig.25 Comparison of the concentrations of five major ions in water samples before and after seawater treatment;
[0054] Fig.26 Schematic diagram of a water-electricity cogeneration device driven by solar energy;
[0055] Fig. 27 The water evaporation mass loss curve when DF / TDT-2 and DF / TABQ-2 are used as evaporators in the water-power cogeneration process;
[0056] Fig.28 The open circuit voltage and short circuit current output of DF / TDT-2 and DF / TABQ-2 when used as evaporators in the water-power cogeneration process;
[0057] Fig.29 It is the output power curve of the water-power cogeneration device under external load. DETAILED DESCRIPTION
[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention and should not be used to limit the protection scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0059] Example 1 Synthesis of Compounds of Formula (I)
[0060] The specific preparation steps are as follows:
[0061] A mixture of tetraaminobenzoquinone (TABQ, 100 mg), tetrabutylammonium bromide (TBABr, 750 mg) and N,N-dimethylformamide (DMF, 15 mL) was placed in a pressure tube and ultrasonicated for 1 min, and then the pressure tube was placed in an oven and heated at 120°C for 12 h. After the reactants were cooled to room temperature, they were filtered or centrifuged to obtain a residue. After multiple washings with DMF and ethanol and drying, 58 mg of black solid 2,3,7,8-tetraamino-5,10-dihydrophenazine-1,4,6,9-tetraketone (TDT, i.e., compound of formula (I)) was obtained.
[0062] The prepared biosolid state of the compound of formula (I) was obtained by using a JEOL nuclear magnetic resonance spectrometer of type JNM-ECZ600R / M1. 13 C nuclear magnetic resonance (NMR) spectrum, solid NMR test as attached Figure 1 The structure of the compound of formula (I) can be confirmed by using a ThermoNicolet IS50 Fourier transform infrared spectrometer to measure the infrared spectrum (FT-IR) of the compound of formula (I). Figure 2 As shown, the structure of the compound of formula (I) can be further confirmed.
[0063] Example 2: SEM characterization, EDS characterization and XPS characterization of the compound of formula (I)
[0064] The microscopic morphology and elements of the compound of formula (I) were analyzed. Scanning electron microscope (SEM) and energy spectrum (EDS) analysis of the compound of formula (I) were performed using a Regulus 8100 scanning electron microscope and an X-ray spectrometer. Figure 3 As shown in the figure, TDT has a rod-like structure with burrs and delamination, and the surface is relatively rough. EDS mapping analysis of the elements is performed, as shown in the attached figure. Figure 4 As shown, the compound of formula (I) contains C, N, and O elements. The element content is further quantitatively analyzed by X-ray photoelectron spectroscopy (XPS), as shown in the attached Figure 5 As shown, the atomic percentages of C, N, and O elements in the compound of formula (I) are 54.44%, 27.42%, and 17.14%, respectively, which are close to the theoretical values of 54.55%, 27.27%, and 18.18%, further verifying the molecular structure.
[0065] Example 3: Photophysical properties of compounds of formula (I)
[0066] The raw material TABQ and the TDT solid powder of the compound of formula (I) synthesized above were characterized by ultraviolet visible near infrared (UV-VIS-NIR) absorption spectrum using a UV-3600Plua spectrophotometer. Figure 6As shown in the figure, compared with the absorption spectrum range of raw material TABQ in the range of 250-1350nm, the absorption spectrum of TDT is broadened, with strong light absorption between 250-1840nm, and the light absorption capacity is significantly enhanced. Figure 7 As shown in the figure, the optical band gap width of TDT is calculated to be 0.77 eV, which is much smaller than the optical band gap of TABQ (1.04 eV). The reduction of the band gap verifies the broadening of the absorption spectrum. On the other hand, the solid fluorescence spectrum and fluorescence quantum efficiency of the compound of formula (I) were measured using an FLS1000 steady-state transient fluorescence spectrometer. Figure 8 As shown, under 600nm wavelength light excitation, the fluorescence quantum yield of TDT in the solid state is negligible, only 0.32%. The low fluorescence emission also indirectly proves that the energy deactivation pathway after the molecule absorbs light energy will be mainly non-radiative transition (i.e., generating heat energy).
[0067] Example 4: Photothermal conversion performance test of the compound of formula (I)
[0068] In order to evaluate the photothermal conversion performance of the molecule, a FOTRIC 288+ thermal imager was used to monitor the temperature change of the molecule powder under simulated sunlight (provided by a CEL-S500-T5 xenon lamp light source) in real time. Fig. 9 As shown, at a light intensity of 1kWm -2 Under the light irradiation, the temperature of TDT rises rapidly and finally stabilizes at 68℃. Then, after turning off the light source, the temperature of TDT gradually drops to room temperature. In addition, the maximum stable temperature is proportional to the light intensity. The greater the light intensity, the higher the temperature. Fig.10 As shown, at 4kW m -2 The maximum temperature under light can reach 140°C. Photothermal materials should not only have good light-to-heat conversion capabilities, but also have excellent resistance to photobleaching. Fig.11 As shown in the figure, the light source is tested by intermittent switching, and it can be found that the maximum temperature remains basically unchanged. Fig.12 As shown, when TDT powder was subjected to continuous illumination (2 hours), the maximum temperature did not decrease or fluctuate significantly, demonstrating good resistance to photobleaching.
[0069] In addition, pure water (0.3 mL), TABQ aqueous dispersion (concentration: 1 mg mL -1 ,0.3mL), TDT aqueous dispersion (concentration: 1mg mL -1 ,0.3mL) under simulated sunlight, and calculate the photothermal conversion efficiency. The solution was placed in a quartz tank with an inner diameter of 1cm wrapped in heat-insulating polystyrene foam, and the temperature of the solution surface within 10 minutes was recorded with a thermal imager. The photothermal conversion efficiency η was calculated as follows:
[0070]
[0071] Where ΔQ is the heat energy generated, Q1 is the heat generated by TABQ or TDT aqueous solution after absorbing light, Q2 is the heat generated by pure water, and E is the total energy of the incident light.
[0072] Q=CmΔT=CρVΔT
[0073] Where C, m, ρ, V, and ΔT are the heat capacity, mass, density, volume, and temperature difference of the solution, respectively.
[0074] E=PSt
[0075] E is determined by the incident light power P, the irradiation area S and the irradiation time t.
[0076] In the experiment, due to the low dispersion concentration of TABQ and TDT, the C and ρ of TABQ and PDI-DTMA solutions used in the calculation were 4.2 J g, respectively. -1 ℃ -1 and 1g cm -3 , the same as pure water. Fig.13 Based on the data recorded in, the photothermal conversion efficiency can be calculated as follows:
[0077]
[0078] Therefore, TDT has better light-to-heat conversion effect. -2 Under the simulated light source, its photothermal conversion efficiency is as high as 26.75%.
[0079] Example 5: Application of the compound of formula (I) in solar-driven thermoelectric conversion
[0080] Photothermal materials can achieve efficient “light-heat-electricity” conversion by coupling thermoelectric devices. Fig.14 The thermoelectric power generation device shown in the figure tests the feasibility of using TDT powder as a solar light absorber to induce thermoelectric power generation. Under sunlight, the top of the thermoelectric module device is heated to a high temperature due to the effective photothermal conversion of TDT, while the bottom of the device is kept at a lower temperature by circulating water. As a result, the temperature difference between the top and bottom of the device induces the Seebeck effect and generates electricity. First, we tested the thermoelectric device (SP1848-27145-SA, size: 40*40*3.6mm 3 ) The performance of the device is evaluated by the electrical output under different configurations and different light intensities. Fig.15As shown in the figure, the signal of the device with photothermal material is significantly larger than that of the blank device without photothermal material, which proves that the photothermal material can achieve more energy acquisition by providing a larger temperature difference. In addition, since TDT has better photothermal performance than TABQ, the open circuit voltage and open circuit current of the device with TDT as the light absorber are larger than those of TABQ. In addition, the electrical signal is correlated with the light intensity, 2kW m -2 The device electrical signal under irradiation is 1kW m -2 Finally, the stability of the device’s power generation was verified by long-term testing. The device with TDT as the photothermal material was tested at 1kW m -2 Test the open circuit voltage and short circuit current under light for 1 hour. Fig.16 As shown, there is no obvious change in the electrical signal during the long-term test, proving that the device has excellent power generation stability. The above results all prove that TDT can generate photothermal energy as a light absorber, and use this heat to provide the required temperature difference for the thermoelectric device, providing ideas for achieving efficient light-heat-electricity conversion.
[0081] Example 6: Preparation of an evaporator system containing a photothermal material of a compound of formula (I)
[0082] The specific preparation is as follows:
[0083] Use dust-free cloth (DF) as the carrier membrane material, clean it with ethanol and dry it before use. Disperse 2.25, 4.5, 9, 18, 27, and 36 mg of TDT powder in 5 mL of ethanol solution and ultrasonicate for 10 min. Use a dropper to evenly drop the TDT suspension onto a 3*3 cm 2 After the ethanol is completely volatilized, the evaporator containing the photothermal material of the compound of formula (I) is prepared, and the loading amounts are 0.25, 0.5, 1, 2, 3, and 4 mg / cm -2 , named DF / TDT-0.25, DF / TDT-0.5, DF / TDT-1, DF / TDT-2, DF / TDT-3, DF / TDT-4. The same preparation method can also be used to prepare an evaporator system containing raw material TABQ.
[0084] Example 7: Characterization and photothermal performance of the evaporator system containing the photothermal material of the compound of formula (I)
[0085] The evaporator containing the photothermal material of the compound of formula (I) was characterized. Fig.17 As shown in the figure, the scanning electron microscope image shows that compared with the smooth fiber surface inside the blank dust-free cloth DF, the internal fiber of the evaporator DF / TDT containing the photothermal material of the compound of formula (I) becomes rough due to the large amount of TDT particles loaded. Fig.18As shown in the figure, X-ray photoelectron spectroscopy (EDS) scans the elements and shows that C, N, and O are distributed in DF-TDT. The uniform distribution of N also shows that TDT nanoparticles are evenly distributed in the DF fiber network. Due to the three-dimensional fiber network structure inside the fabric, the incident light can be reflected multiple times on the fiber surface, which can effectively inhibit light escape, thereby significantly increasing light absorption and reducing light reflection. In addition, TDT has excellent light absorption properties, such as the attached Fig.19 As shown in Figure 2, DF / TDT exhibits broad and strong absorption in the wavelength range of 300-2500 nm. -2 Under simulated sunlight, a thermal imager was used to detect the temperature rise of the sample. Fig. 20 As shown in the figure, all fabric samples can heat up quickly and reach a stable state in about 1 min. The maximum temperature of the dry dust-free cloth DF rises to 37.2 °C. The photothermal stability temperature of DF / TDT increases with the TDT loading (0-2 mg cm -2 ) increases with the increase of the loading amount, where 2 mg cm -2 The maximum temperature of DF / TDT-2 can reach 70.6℃. As the TDT loading increases further, the maximum temperature remains basically unchanged. The above excellent photothermal performance provides conditions for subsequent applications.
[0086] Example 8: Application of an evaporator system containing a photothermal material of a compound of formula (I) in solar-driven interfacial water evaporation
[0087] The evaporator containing the photothermal material of the compound of formula (I) is placed in the following Fig.21 The solar-driven water evaporation performance was tested in the evaporation system shown in the figure. -2 ) irradiation, the weight loss caused by water evaporation is monitored in real time using a balance, from which the evaporation rate can be calculated. As shown in Figure 22, the evaporation rate of pure water is only 0.44 kg m - 2 h -1 The evaporation rate of the dust-free cloth without photothermal material, i.e. DF, is 0.62 kg m -2 h -1 In contrast, the evaporation rate of the evaporator system containing the photothermal material of the compound of formula (I), i.e., the DF / TDT system, was significantly improved. As the loading amount of the photothermal material of the compound of formula (I) increased, the corresponding evaporation rate of the evaporator was improved. When the loading amount was 2-4 mgcm -2 When the loading amount is 2 mg cm -2 The DF / TDT-2 evaporator achieves 1.54 kg m -2 h -1The high evaporation rate is comparable to other inorganic solar thermal materials. More importantly, Fig.23 As shown, its evaporation performance is relatively advanced among the same type of organic small molecule-based two-dimensional planar film evaporators, and is even not inferior to the evaporation rate of organic small molecule-based three-dimensional evaporators.
[0088] Example 9: Application of an evaporator system containing a photothermal material of a compound of formula (I) in sewage treatment
[0089] The water in the solar-driven water evaporation system in Example 8 was replaced with simulated sewage to test the sewage treatment capacity of the DF / TDT-2 system under light. Cr2(SO4)3, Cu(NO3)2, Ni(NO3)2, CdSO4, and Pb(CH3COO)2 were dissolved in deionized water to prepare a Cr-containing 3+ , Cu 2+ 、Ni 2+ 、Cd 2+ , Pb 2+ The simulated sewage was filled with heavy metal ions. The initial sewage and steam condensate samples were tested separately to evaluate the ion removal effect. The changes in ion concentrations in the simulated sewage samples before and after treatment were monitored using inductively coupled plasma mass spectrometry / optical emission spectrometry (ICP-MS / OES). Fig.24 As shown, Cr 3+ , Cu 2+ 、Ni 2+ 、Cd 2+ , Pb 2+ The concentrations of the five ions decreased from 46.2, 37.5, 59.3, 98.3, and 41.2 to 0.0954, 0.0229, 0.0599, 0.1093, and 0.0403 mg L after desalination. -1 , the ion removal rate is not less than 99.7%. This result shows the great potential of the evaporator system containing the photothermal material of the compound of formula (I) in sewage treatment applications.
[0090] Example 10: Application of an evaporator system containing a photothermal material of the compound of formula (I) in seawater desalination
[0091] The water in the solar-driven water evaporation system in Example 8 was replaced with seawater to test the desalination capacity of the DF / TDT-2 system under illumination. The ion removal effect was evaluated by testing the condensed water samples of the initial seawater and steam condensation. The changes in ion concentrations in the water samples before and after treatment with real Yellow Sea water were monitored using inductively coupled plasma mass spectrometry / optical emission spectroscopy (ICP-MS / OES). As shown in Figure 25, Na + Mg 2+ , Ca 2+ , K+ , B 3+ The concentrations of the five ions dropped sharply from 9594.5, 1216.6, 352.0, 388.6, and 3.6 to 3.075, 0.316, 0.099, 0.269, and 0.016 mg L after desalination. -1 , the ion removal rate is not less than 99.6%. This result shows the great potential of the evaporator system containing the photothermal material of the compound of formula (I) in the application of seawater desalination.
[0092] Example 11: Application of an evaporator system containing a photothermal material of the compound of formula (I) in solar-driven water-electricity cogeneration.
[0093] Combining solar-driven photothermal interface evaporation and thermoelectric conversion can build a solar-driven water-electricity cogeneration system. Fig.26 As shown in the figure, polystyrene foam is used to fix and support the thermoelectric device and the evaporator containing the photothermal material. Under light, the temperature of the upper surface of the evaporator (the part containing the photothermal material) increases, which can be used to promote water evaporation and provide a high temperature environment for the hot end of the thermoelectric device. The cold end of the thermoelectric device is in contact with water to achieve a low temperature environment. The loading amount of TDT and TABQ for the photothermal material is 2mgcm -2 The hydropower cogeneration system constructed by the two companies (named: DF / TDT-2 and DF / TABQ-2) was tested for the simultaneous production of water and electricity. Fig. 27 As shown, at 1.0kW m -2 Under simulated sunlight, the water evaporation rates of DF / TDT-2 and DF / TABQ-2 systems were 1.17 and 1.02 kg m –2 h –1 At the same time, as attached Fig.28 As shown in the figure, the maximum open circuit voltage and short circuit current of the DF / TDT-2 and DF / TABQ-2 systems are 86.16mV, 13.04mA and 70.34mV, 11.20mA respectively. The DF / TDT-2 system is further connected with an external load resistor to measure the output power of the device. As the load resistance increases, the output current decreases, while the output voltage increases. Therefore, as shown in the attached figure, Fig.29 As shown in the figure, when the external load resistance is 4Ω, the system has the maximum output power density, which is about 0.27W m -2 .
[0094] Although the present invention is described using the above embodiments, it should be understood that the present invention may be further modified and varied without departing from the spirit of the present invention, and these modifications and variations are all within the scope of protection of the present invention.
Claims
1. An organic small molecule photothermal material, characterized in that: The organic small molecule photothermal material is a compound represented by formula (I):
2. An evaporator system for small organic molecules, characterized in that: It comprises a compound represented by formula (I) and a carrier material, wherein the compound represented by formula (I) has the following structural formula: The carrier material is one of a film material, a foam material or a hydrogel material.
3. The organic small molecule evaporator system according to claim 2, characterized in that: The membrane material is at least one of dust-free cloth, non-woven fabric, electrospun nano-membrane and cellulose paper.
4. A method for preparing an evaporator system for organic small molecules, characterized in that: The preparation method comprises the following steps: washing the membrane material with ethanol and drying it; dispersing the powder of the compound represented by formula (I) in ethanol, ultrasonicating for 10-30 minutes, then evenly dripping or brushing the suspension on the dried membrane material, and finally drying it, thereby preparing an evaporator system containing the photothermal material represented by formula (I).
5. A water-power cogeneration device, characterized in that: The compound as shown in formula (I) is covered in the middle of the carrier, the middle part of the carrier is fixed on the upper surface of the thermoelectric device, and the carrier parts without the compound as shown in formula (I) at both ends are in contact with the water body, and polystyrene foam is used as a supporting part to fix the thermoelectric device, so that the lower part of the thermoelectric module contacts the water surface; The structural formula of the compound shown in formula (I) is as follows:
6. The water-power cogeneration device according to claim 5, wherein the carrier is one of dust-free cloth, non-woven fabric, electrospun nanofilm and cellulose paper.
7. Use of the small molecule photothermal material as claimed in claim 1 in the preparation of a photothermal conversion layer or a photothermal functional molecular material.
8. Application of the organic small molecule photothermal material as claimed in claim 1 in solar-driven thermoelectric conversion, interfacial photothermal evaporation, water-power cogeneration, sewage treatment and seawater desalination.
9. Application of the organic small molecule evaporator system as described in claims 2-3 in solar-driven interfacial photothermal evaporation, thermoelectric conversion, water-power cogeneration, sewage treatment and seawater desalination.
10. Application of the water-power cogeneration device as claimed in claims 2-3 in water-power cogeneration.